Performance of Recycled Aggregate Concrete Containing Micronised Biomass Silica - Hani Adnan, Suraya; Abdul Rahman, Ismail; Loon, Lee Yee (International Journal of Sustainable Construction Engineering and Technology, 2011)
This paper presents a study on Micronised Biomass Silica (MBS) that was produced from the controlled burning of waste Rice Husk. The MBS was used as pozzolan material to enhance the performance of Recycled Aggregate Concrete (RAC). Various percentages by mass of Micronised Biomass Silica were applied in the normal and recycled aggregate concrete cube samples. Compressive strength and water permeability tested on the samples at the age of 7, 14, 28 and 90 days showed that concrete containing MBS has attained higher compressive strength. Furthermore, the test on MBS also showed its ability to enhance the concrete water permeability. Lengthen to this; the study established a good correlation between the MBS content with compressive strength and water permeability coefficient.